DAMPAK PENGGUNAAN DIVIGO TERHADAP HASIL BELAJAR MATEMATIKA PADA MATERI PEMBAGIAN BILANGAN CACAH SISWA KELAS III SEKOLAH DASAR - Silvia Fitriani; Rayi Siti Fitriani; Wina Mustikaati (STKIP Subang, 2026)
Elementary schools continue to struggle with poor whole number division learning outcomes, primarily as a result of teacher-centered education and pupils' inability to grasp the abstract idea of division. In order to solve this problem, the researcher created DIVIGO, an instructional board game that uses a game-based learning methodology to help third-grade pupils grasp whole number division. The objectives of this study were to: (1) compare pretest scores between the experimental and control groups prior to DIVIGO implementation, (2) compare posttest scores following DIVIGO implementation, (3) compare learning improvement between the two groups, and (4) determine the impact of DIVIGO on learning outcomes in mathematics. The sample consisted of 64 third-grade students from SDN Pasawahan Kidul, Purwakarta, divided into an experimental class and a control class (32 students receiving conventional instruction). Pretests and posttests were used to gather data, and descriptive statistics, the Shapiro-Wilk normality test, Levene's homogeneity test, the Mann-Whitney U test, the Independent Samples t-test, and Cohen's d effect size were used for analysis. The findings showed: (1) a significant difference in pretest scores (Mann–Whitney U, p = 0.003), with the control class showing higher initial ability; (2) a significant difference in posttest scores (p = 0.010), with the experimental class attaining a higher mean score (72.06) than the control class (56.19); (3) a significant difference in learning improvement (p = 0.025); and (4) a moderate effect, as indicated by a Cohen's d value of 0.666. These results show that DIVIGO enhances third-grade pupils' whole number division learning outcomes.